Service Recovery Satisfaction in Open and Distance Learning (ODL) in Malaysia: Antecedents and Outcomes - Mohd Rushidi bin Mohd Amin; Shishi Kumar Piaralal; Zahir Osman; Abdul Rahim Mohamed Amin (ASEAN Journal of Open and Distance Learning, 2018)
Researchers and practitioners often pay less attention to service recovery research compared to service quality or customer satisfaction, particularly in the context of Open and Distance Learning. Moreover, the antecedents and outcomes of service recovery satisfaction are frequently given less emphasis by Open and Distance Learning institutions in their efforts to gain advantages in the current higher education business environment. Service organisations such as Open and Distance Learning institutions are often focused on delivering services with the approach of getting it right the first time. Service failure is inevitable and when service delivery fails at some point, the whole process will be disrupted and the students will be dissatisfied and disappointed. This is where service recovery satisfaction through justice dimensions plays its role. This study explores the relationship between justice dimensions (Distributive, Procedural, Interpersonal and Informational Justice) and Service Recovery Satisfaction, in addition to examining the moderating effects of University Image. In order to regain lost customer support, service providers must overcome the negative impact of poorly performed service. Previous studies have attempted to identify the impact of service recovery satisfaction by analysing the variation in post-recovery customer outcomes. The present study explores four customer outcomes: Repurchase Intention, Word of Mouth, Trust and Loyalty within the Malaysian ODL context. (Abstract by authors)